Vold i nære relasjoner i et mangfoldig Norge - Bredal, Anja; Eggebø, Helga; Eriksen, Astrid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"Research, politics and activism have traditionally emphasized gender in understanding and combating domestic violence. In recent years, however, increasing attention has been placed on other social factors. This anthology presents new research that elucidates domestic violence from more diverse perspectives. In the nine chapters, the contributors analyze how types and degrees of violence and abuse can vary depending upon the interplay between such different factors as class, ethnicity, gender and sexual orientation. An overarching theme is how we understand and talk about equality, difference and diversity. The book does not provide an exhaustive analysis of violence in today's multi-cultural Norway, yet it is the first Norwegian book about domestic violence that has diversity as a primary them. The book will be of interest to researchers, students, employees in social services and support organizations and anyone concerned about domestic violence and abuse."